Socioeconomic factors associated with limb salvage versus amputation for adult extremity bone sarcomas in patients with insurance coverage. (December 2021) - Houdek, Matthew T.; Stuart, Michael B.; Wellings, Elizabeth P.; Wagner, Eric R.; Asante, Dennis; Sangaralingham, Lindsey R.; Rose, Peter S.; Moran, Steven L.
Abstract: Background: Limb salvage (LS) has become the preferred treatment for adult patients with bone sarcoma of the extremities. The decision to perform LS versus an amputation is often dictated by tumor characteristics, however there may be socioeconomic factors associated with LS. Previously this has been linked to insurance status, however currently there is a paucity of data examining socioeconomic factors in patients with medical insurance at the time of sarcoma diagnosis. Therefore, the purpose of the current study was to examine socioeconomic factors which could be associated with the decision to perform LS versus amputation for adult bone sarcoma patients. Methods: Data from Optum Labs Data Warehouse, a national administrative claims database, was analyzed to identify patients with extremity bone sarcomas from 2006 to 2017. Bivariate regression was used to identify factors associated with LS versus amputation. Results: Of 1, 390 (743 males, 647 female) patients, 252 (18%) under amputation while 1, 138 (82%) underwent LS. Lower extremity tumors (OR 4.72, p < 0.001), income <75, 000 (OR 1.85, p = 0.03), being treated a public hospital (OR 1.41, p = 0.04) and a hospital with <200 beds (OR 1.90, p = 0.006) were associated with amputation. Income ≥125, 000 (OR 0.62, 0.04) were associated with LS. Conclusion: In adult patients with medical insurance at the time of diagnosis, socioeconomic and hospital factors were associated with an amputation for bone sarcoma, with poorer patients, and those treated at smaller, and public hospitals more likely to undergo amputation. Highlights: Insurance status is not protective of socioeconomic disparities in limb salvage surgery. Low household income, treatment at small and public hospitals was associated with amputation. Further work is needed to identify socioeconomic disparities in this patient population.